Dose‐dependent effects of ethanol extract of Salvia haematodes Wall roots on reproductive function and copulatory behaviour in male rats. (12th March 2014) - Bansode, F. W.; Rajendran, S. M.; Singh, R. K.
Summary This study was aimed to investigate the dose‐dependent effects of Salvia haematodes Wall roots (SHW) extract on male reproductive function and copulatory behaviour in rats. Sexually mature males were assigned to four groups: control and treated (5, 50 and 300 mg kg−1 day−1 for 30 days). At the end of treatment regimes, the reproductive activity viz. body/organ weights, testicular spermatogenesis, daily sperm production rate (DSP) and epididymal sperm counts, and sexual behaviour including mounting latency (ML), mounting frequency (MF), intromission latency (IL), intromission frequency (IF), ejaculation latency (EL), post‐ejaculatory interval (PEI) and penile reflexes (PE) were assessed. Results showed significant increase in body weight (at 300 mg kg−1), testis/epididymis weights (at 50 and 300 mg kg−1), testicular spermatids, DSP, tubular diameter and epididymal sperm counts (at 50 and 300 mg kg−1doses) in treated compared with control rats. It also produced dose‐dependant changes in sexual behaviour. The 5 mg kg−1 dose of extract increased MF and PE, whereas 50 and 300 kg−1 doses caused significant increase in MF, IF, PE, EL (but less than sildenafil citrate treatment), hit rate and seminal plug weight. It is concluded that SHW extract enhances anabolic activity, testicular function and sexual behavioural performance in a dose‐dependant manner.